2016
DOI: 10.1590/1983-084x/15_222
|View full text |Cite
|
Sign up to set email alerts
|

Atividade antifúngica e possível mecanismo de ação do óleo essencial de folhas de Ocimum gratissimum (Linn.) sobre espécies de Candida

Abstract: RESUMO:A espécie Ocimum gratissimum (Linn.), popularmente conhecida como alfavacacravo, é muito utilizada na medicina popular. A planta apresenta inúmeros compostos, sendo o eugenol o constituinte majoritário do seu óleo essencial e o provável responsável pela sua atividade antimicrobiana. O objetivo deste estudo foi determinar o potencial antifúngico e o possível mecanismo de ação do óleo essencial extraído das folhas de O. gratissimum L. (OEOg) sobre cepas-padrão de Candida. Para avaliação da atividade antim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 20 publications
0
10
0
4
Order By: Relevance
“…The microplate was incubated for 24 to 48 h in an incubator at 37 °C and resazurin was added to determine microbial growth 53 . The MIC for yeast was determined by a modified broth microdilution method 54 .…”
Section: Methodsmentioning
confidence: 99%
“…The microplate was incubated for 24 to 48 h in an incubator at 37 °C and resazurin was added to determine microbial growth 53 . The MIC for yeast was determined by a modified broth microdilution method 54 .…”
Section: Methodsmentioning
confidence: 99%
“…Brito et al (2015), showed that the C. krusei and C. tropicalis strains cultivated in culture medium in the presence of the Lippia sidoides (Verbenaceae) essential oil did not present pseudohyphae and hyphae at the 256 μg/mL concentration. Meanwhile, Oliveira, Batista, Fernandes, Sales, and Nogueira (2016) showed a reduction in C. albicans hyphae at the 1.25 mg/mL and 2.5 mg/mL concentrations, as well as C. albicans (0.625 mg/mL and 2.5 mg/mL) and C. parapsilosis (1.25 mg/mL and 2.5 mg/mL) treated with the Ocimum gratissimum (Lamiaceae) essential oil.…”
Section: Antifungal Activitymentioning
confidence: 99%
“…L. monocytogenes is known to cause the disease listeriosis, which affects principally immunocompromised patients, thereby having a mortality rate of 30%. Furthermore, the bacteria bear the ability for biofilm formation, and by this way developing resistance to sanitizers and antimicrobial agents, thus provoking serious problems to food industries (Oliveira et al, 2016b;Rogalla and Bomar, 2018;Marini et al, 2018).…”
Section: Introductionmentioning
confidence: 99%